A STRENGTH-NORMALISED FRAMEWORK FOR COMPARING COBBLESTONE AND ASPHALT CONCRETE WEARING COURSES IN LOW-SPEED URBAN ROADS - Kamala, Derick; Mlodi, Lodgar (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2026)
Low-speed urban road sections such as intersections, bus bays, parking areas, and braking zones are subjected to high contact stresses, frequent braking, and moisture exposure, conditions that often lead to rutting, deformation, and strength degradation in conventional asphalt wearing courses. Although cobblestone pavements have historically demonstrated durable performance in similar environments, their application remains largely based on empirical practice rather than systematic mechanical comparison with asphalt materials. This study proposes a strength-normalized performance framework to compare the mechanical suitability of cobblestone and dense-graded asphalt concrete wearing courses for low-speed urban applications. Cobblestone performance was characterized using aggregate crushing, impact, and abrasion tests representing compressive resistance, impact toughness, and abrasion durability. Asphalt mixture performance was evaluated using Marshall stability, indirect tensile strength, and unconfined compressive strength to represent shear, tensile, and compressive resistance. Test results were normalized into dimensionless indicators and integrated into composite strength indices reflecting dominant pavement stress modes. Results show that cobblestone achieved a strength index of 1.317, compared with 1.102 for asphalt under dry conditions, indicating approximately 20% higher resistance to compression- and wear-dominated loading. Under soaked conditions, the cobblestone index decreased to 1.152, approaching asphalt performance